Nutrition Knowledge, Attitudes, and Confidence of Australian General Practice Registrars. (5th August 2015) - Nowson, Caryl A.; O'Connell, Stella L.
Abstract : Nutrition knowledge, attitudes, and confidence were assessed in General Practice Registrars (GPRs) throughout Australia. Of approximately 6, 000 GPRs invited to complete a nutrition survey, 93 respondents (2%) completed the online survey, with 89 (20 males, 69 females) providing demographic and educational information. Fifty-one percent had graduated from medical school within the last two years. From a list of 11 dietary strategies to reduce cardiovascular risk, respondents selected weight loss (84%), reducing saturated fats (90%), a maximum of two alcoholic drinks/day (82%), and increasing vegetables (83%) as "highly appropriate" strategies, with only 51% indicating that salt reduction was "highly appropriate." Two-thirds of registrars felt "moderately" (51%) or "very" confident (16%) providing nutrition advice. Most of them (84%) recalled receiving information during training, but only 34% recalled having to demonstrate nutritional knowledge. The results indicate that this group of Australian GPRs understood most of the key dietary recommendations for reducing cardiovascular risk but lacked consensus regarding the recommendation to reduce salt intake and expressed mixed levels of confidence in providing nutritional advice. Appropriate nutrition education before and after graduation is recommended for GPRs to ensure the development of skills and confidence to support patients to make healthy dietary choices and help prevent chronic diseases.